2022
DOI: 10.21809/rilemtechlett.2022.139
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of rheology in the plastic settlement and shrinkage cracking of early age concrete

Abstract: Understanding the plastic (settlement/shrinkage) cracking phenomena of early-age concrete is important in-order to establish a holistic approach to minimise its occurrence. One of the factors associated with early-age concrete is the rheo-related behaviour which occur simultaneously within the timeframe known for plastic cracking. It is therefore useful to establish their links to broaden the knowledge of plastic cracking. This study is a novel evaluation of the influence of rheo-physical and rheo-viscoelastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…However, coupled with the multiple regression Model IV, it is demonstrated that an inverse relationship exists between yield stress and plastic cracking. It may be that, as Kalovole highlighted, high-yield stress causes the capillary pressure and shrinkage to increase, and therefore, for a mixture with fly ash, a high G value is a factor of a decrease in cracking resistance [39]. This argument is consistent with the study [60], which states that the addition of small particle-size fillers increases capillary pressure.…”
Section: Discussion Of the Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…However, coupled with the multiple regression Model IV, it is demonstrated that an inverse relationship exists between yield stress and plastic cracking. It may be that, as Kalovole highlighted, high-yield stress causes the capillary pressure and shrinkage to increase, and therefore, for a mixture with fly ash, a high G value is a factor of a decrease in cracking resistance [39]. This argument is consistent with the study [60], which states that the addition of small particle-size fillers increases capillary pressure.…”
Section: Discussion Of the Resultssupporting
confidence: 72%
“…In addition, an increase in the early tensile strength of the SF mixture at high capillary pressure was asserted [59]. Therefore, it is possible to conclude, according to Kalovole [39], that the high-yield stress of silica fume mixtures increases the capillary pressure, and hence, the risk of plastic cracking is increased by the high flow resistance. However, the acceleration of the hydration effect by silica fume [63,64] and the addition of a water reducer stopped the plastic cracking development.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation